DEVELOPMENT OF FUNCTION FACILITIES AT FISH MARKETING PLACE IN PAKNING ASAL BUKIT BATU, BENGKALIS, RIAU PROVINCE - Silaban, Adelina; Polaris, Polaris; Jonny, Jonny (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe purpose of this study is to determine the type and size of land facilities that should exist for the exist for the smoothness of fishing activities and their possible development. The study was conducted in September 2017. The method used in this research is survey method. Data analysis using facility requirement analysis. The survey indicatesthat existing land facilities are rig, fleet repair and fishing gear. The existing functional facilities at the Pakning Asal fish marketing place consist of rig and shipyard. The available facility of rig is 41,65 m2, while the required is 45,15 m2. Fuel tank facility with capacity of 139 liter of diesel, 360 liters for fresh water capacity, and 240 kg per one production for production capacity of ice storage. Â Keywords: fish marketing place, functional facilities, size development